Debate Over the Economic Role of the State in Poland in the Works of the Representatives of the Kraków School, the Leviathan Organization and the First Economic Brigade in the Years 1919–1939 - Jarosz-Nojszewska, Anna (Studia Historiae Oeconomicae, 2017)
As Poland regained independence in 1918, it immediately had to deal with the question of how to shape its political and economic system. One important but at the same time controversial issue was the level of the state’s involvement in the economic life of the country and the measures used. In numerous debates among economists, the dominant topics included problems in the industry - in particular issues such as statism, monopolization, policy towards cartels and, in the later period, economic planning. The article presents the course of the discussion on the role of the state in the economy that took place in Poland in the years 1918-1939, as well as a review of arguments put forward by the proponents and opponents of state’s economic interventionism. For the purpose of this article, three groups that were most active in the debate were selected: the Kraków School, the Leviathan organization and the First Economic Brigade.